2010 IEEE Antennas and Propagation Society International Symposium 2010
DOI: 10.1109/aps.2010.5560911
|View full text |Cite
|
Sign up to set email alerts
|

2.45 GHz end-loaded dipole backed by a high impedance surface

Abstract: An end loaded planar open sleeve dipole (ELPOSD) antenna over an electromagnetic band gap (EBG) high impedance surface is presented. An ELPOSD consists of a printed dipole with two parasitic elements (sleeves) along its sides and capacitive loading at the end. This antenna is fed from beneath the ground plane by live vias connected to a microstrip to coplanar strip balun. The EBG structure is based on the Jerusalem Cross geometry and is sandwiched between two 1.27 mm-thick substrate layers, resulting in a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…1). Previous works have demonstrated that dipole-type antennas above FSS ground planes tend to be narrowband [1], [2]. In [2] it was shown via simulation that the bandwidth can be increased by positioning the dipole in free space above the FSS; the typical bandwidth with this approach is 4.3% for a total antenna and FSS thickness of ~λ/25.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1). Previous works have demonstrated that dipole-type antennas above FSS ground planes tend to be narrowband [1], [2]. In [2] it was shown via simulation that the bandwidth can be increased by positioning the dipole in free space above the FSS; the typical bandwidth with this approach is 4.3% for a total antenna and FSS thickness of ~λ/25.…”
Section: Introductionmentioning
confidence: 98%
“…The primary objective of this effort is to study the impact on antenna bandwidth and planar size when capacitive loading is introduced into the FSS. This work builds upon the design presented by Cure [1] with the goal of achieving bandwidths on the order of 10%.…”
Section: Introductionmentioning
confidence: 99%